Cretaceous and Paleogene Fagaceae from North America and Greenland: evidence for a Late Cretaceous split between Fagus and the remaining Fagaceae - Grímsson Friðgeir; Grimm Guido W.; Zetter Reinhard; Denk Thomas (Acta Palaeobotanica, 2016)
Modern lineages of the beech family, Fagaceae, one of the most important north-temperate families of woody flowering plants, have been traced back to the early Eocene. In contrast, molecular differentiation patterns indicate that the Fagus lineage, Fagoideae, with a single modern genus, evolved much earlier than the remaining lineages within Fagaceae (Trigonobalanoideae, Castaneoideae, Quercoideae). The minimum age for this primary split in the Fagaceae has been estimated as 80 ± 20 Ma (i.e. Late Cretaceous) in recently published, time-calibrated phylogenetic trees including all Fagales. Here, we report fagaceous fossils from the Campanian of Wyoming (82-81 Ma; Eagle Formation [Fm]), the Danian of western Greenland (64-62 Ma; Agatdal Fm), and the middle Eocene of British Columbia (ca 48 Ma; Princeton Chert), and compare them to the Fagaceae diversity of the recently studied middle Eocene Hareøen Fm of western Greenland (42-40 Ma). The studied assemblages confirm that the Fagus lineage (= Fagoideae) and the remainder of modern Fagaceae were diverged by the middle Late Cretaceous, together with the extinct Fagaceae lineage(s) of Eotrigonobalanus and the newly recognised genus Paraquercus, a unique pollen morph with similarities to both Eotrigonobalanus and Quercus. The new records push back the origin of (modern) Fagus by 10 Ma and that of the earliest Fagoideae by 30 Ma. The earliest Fagoideae pollen from the Campanian of North America differs from its single modern genus Fagus by its markedly thicker pollen wall, a feature also seen in fossil and extant Castaneoideae. This suggests that a thick type 1 foot layer is also the plesiomorphic feature in Fagoideae although not seen in any of its living representatives. The Danian Fagus pollen of Greenland differs in size from those of modern species but is highly similar to that of the western North American early Eocene F. langevinii, the oldest known beech so far. Together with the Quercus pollen record, absent in the Campanian and Danian formations but represented ...